1994
DOI: 10.1152/ajpgi.1994.266.6.g1090
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged administration of IGF peptides enhances growth of gastrointestinal tissues in normal rats

Abstract: To investigate the effect of insulin-like growth factor (IGF) peptide infusion on the gastrointestinal tract, female rats (115 g, 6/group) were treated for 14 days with IGF-I or long R (LR3IGF-I; 0, 44, 111, or 278 micrograms/day) delivered by osmotic minipumps. Both peptides induced a dose-dependent increase in gastrointestinal tissue weight. Total gut weight, small intestinal weight, and small intestinal length increased by 43, 47, and 13%, respectively, after treatment with 278 micrograms/day of LR3IGF-I. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
2
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 0 publications
6
64
2
1
Order By: Relevance
“…It stimulates gut epithelial cell proliferation (Chen et al 1991, Steeb et al 1994 and increases gut weight in rats after dexamethasone treatment or partial gut resection . It may also accelerate maturation of gut permeability (McRoberts & Riley 1992) and brush border enzyme maturation in neonatal rats (Young et al 1990, Ma & Xu 1997.…”
Section: Discussionmentioning
confidence: 99%
“…It stimulates gut epithelial cell proliferation (Chen et al 1991, Steeb et al 1994 and increases gut weight in rats after dexamethasone treatment or partial gut resection . It may also accelerate maturation of gut permeability (McRoberts & Riley 1992) and brush border enzyme maturation in neonatal rats (Young et al 1990, Ma & Xu 1997.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal proliferative response to human recombinant IGF-I at doses much higher than that in colostrum has been observed in experiments. Using long R3 IGF-I (LR3IGF-I), an IGF-I analogue with greater biological potency than IGF-I thought to result from its different pharmacokinetic characteristics, Steeb et al [203,204] have demonstrated the remarkable intestinal proliferative response to both a 14-day course and a 3-day course infusion in adult rats. In normal adult rats, a 14-day infusion of LR3IGF-I at 278 Ìg/day (approximately 2.42 mg/kg/day) resulted in an increase in total gut weight by 43%, small intestine weight by 47%, small intestine length by 13%, an increase in crypt depth and villus height with an associated 33% increase in crypt cell population, 34% increase in cells per villus column, and 20% in villus cell density [201].…”
Section: Protein Undernutrition and Nutritionally Regulated Hormonal mentioning
confidence: 99%
“…In this experiment we did not investigate the effect of surgery or IGF-I on the intestinal mucosa. Following resection of the small intestine or colon the administration of IGF-I can produce changes in the wall of the gut, so it was interesting to investigate the effects of major surgery and administration of IGF-I on circulating gastrointestinal hormones and growth factors (Adrian et al 1987, Vanderhoof et al 1992, Steeb et al 1994, WirĂ©n et al 1995, Zhang et al 1995, Inaba et al 1997, Shimoda et al 1997. It has been reported that both enteroglucagon and PYY increase massively following small bowel resection (Armstrong et al 1991).…”
Section: Figure 1 Serum Concentrations Of Igf-i In Patients Given Igfmentioning
confidence: 99%
“…This effect is likely to be mediated by IGF-I, since an increase in IGF-I mRNA was found in the intestinal mucosa in GH-transgenic mice (Ulshen et al 1993). Long-term administration of IGF-I has a positive effect on the growth of the gastrointestinal tract (Steeb et al 1994). This effect is also seen after intestinal resection and transplantation (Vanderhoof et al 1992, Zhang et al 1995.…”
Section: Introductionmentioning
confidence: 99%